Asset Management and Surplus Distribution Strategies in Life Insurance: An Examination with Respect to Risk Pricing and Risk Measurement - Gatzert, Nadine (Insurance Mathematics & Economics, 2008)
In this paper, we investigate the impact of different asset management and surplus distribution strategies in life insurance on risk-neutral pricing and shortfall risk. In general, these feedback mechanisms affect the contract's payoff and hence directly influence pricing and risk measurement. To isolate the effect of such strategies on shortfall risk, we calibrate contract parameters so that the compared contracts have the same market value and same default-value-to-liability ratio. This way, the fair valuation method is extended since, in addition to the contract's market value, the default put option value is fixed. We then compare shortfall probability and expected shortfall and show the substantial impact of different management mechanisms acting on the asset and liability side.
WiSo-Import:2015-03-26:1368
Keywords: Surplus distribution; Lower partial moments; Life insurance; Fair valuation; asset management